Regeneration Status in Natural Habitats of Nageia wallichiana (Presl.) O.Ktz, Goodrical Reserved Forest of Western Ghats of India - Abhilash, E. S.; Menon, A. R. R.; Balasubramanian, K. (Indian Forester, 2005)
A study was conducted in natural habitats of Goodrical Reserved Forest to assess the abundance and diversity of seedling regeneration as a function of Forest Ecosystem. The most dominant species encountered was Palaquium ellipticum (Dalz.) Engl. Based on the distribution pattern except the saplings of study site-I, all categories and sites, Nageia wallichiana (Presl.)O.Ktz. showed contagious distribution but majority of the other species, we can see the preponderance of random distribution. In the case of Nageia wallichiana (Presl.) O.Ktz. a high mortality rate is seen especially from unestablished to established stage. In the study site-II it is noted that the increase in individual percentage of secondary species might have been due to past selection felling operations and has resulted decrease in the individual percentage of endemics and other conservational categories. The habitat is highly diverse in nature and harbours considerable number of endemics and other conservational categories like rare, endangered, vulnerable etc.